KARAKTERISTIK GEOLOGI DAERAH GUNUNGAN LUMPUR CIUYAH - -, Faizal Muhamadsyah; -, Edy Sunardi; -, Vijaya Isnaniawardhani (Fakultas Teknik Geologi Universitas Padjadjaran, 2012)
The mud flow which identified in Ciuyah area is located in Ciniru village, District Ciniru, Kuningan regency, West Java. Study of morphometry through the deployment of slope classes have described the class as a concentric distribution with location of Ciuyah mud flow in the middle. Annular’s drainage pattern at the regional scale is reflected of the circular in the Ciniru area, at around of site Ciniru extrusion Ciuyah mud mound. Circular patterns of distribution shown by the slope zone, and annular flow patterns in the river a more regional scale is suggest updoming beneath the surface. Interpreted that the migration channel and the possible fluid circulation is controlled by faults that developed in the study area. Structural geology are factors that contribute to the release or migration of fluid to the surface, and provide an outlet for material and fluid under conditions of excessive stress, clayey material which forming of bedrock formations is elusiation experience process, and eventually formed mountains of mud intrusion on the surface